The role of Financial Technology by Indonesian Digital Banks - Maya Macia Sari; Noni Ardian (Jurnal Ilmiah Manajemen Kesatuan, 2026)
One of the key pillars supporting the operations of digital banks is cloud computing technology, which enables flexible management of data and applications through the internet. Cloud computing has become an ideal solution for digital banks because it offers efficiency in managing information technology infrastructure. This study aims to examine the use of cloud computing technology by digital banks in Indonesia. A qualitative approach with a case study method was employed to analyze how cloud computing is utilized by Indonesian digital banks. The findings of this study indicate that cloud computing technology has a significantly positive impact on the operations of digital banks in Indonesia. A total of 75% of digital banks reported a reduction in operational costs of up to 30% after adopting cloud computing, while 60% noted improvements in data access speed due to the flexibility of the infrastructure. Service scalability is also a major advantage, with 55% of banks able to increase capacity without making substantial investments in additional infrastructure. Furthermore, the integration of cloud technology with big data and artificial intelligence allows 70% of banks to enhance service personalization, such as more accurate product recommendations and improved fraud detection. However, this study also identifies several key challenges, including data security concerns experienced by 40% of digital banks, as well as compliance with local regulations, which remains an obstacle for 50% of banks.